Game Theory Analysis on Marketing Strategy Determination of KAI Access and Traveloka based on Usability of HCI (Human-Computer Interaction) - Henoch Juli Christanto (Journal of Information System and Informatics, 2022)
In the era of digitalization, KAI finally transformed train ticket booking transactions by launching the KAI Access application. By applying the optimal strategy of Game Theory, KAI Access will be able to compete with marketplaces such as Traveloka to be able to represent itself to the community as a credible company. Game Theory was chosen to analyze the existing competition to find the optimum strategy. Because both applications sell the same product, the strategy will be seen from the services provided by both applications using the usability of HCI. The 5 strategies are Learnability, Efficiency, Memorability, Errors, and Satisfaction. The best strategy used by KAI Access to obtain maximum profit is the low error rate (errors) strategy, while for Traveloka the strategy used to minimize loss is the ease of application (learnability).